Transformasi UMKM: Inovasi Digital sebagai Jalan Menuju Keberlanjutan Bisnis - Jannah, Wildanul Wildanul Jannah (Maliki Interdisciplinary Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy. However, amid globalization and increasingly intense competition, MSMEs face significant challenges. The adoption of digital transformation has become a strategic step to enhance competitiveness while ensuring business sustainability. This study aims to analyze how digital innovation, through the utilization of technologies such as e-commerce, fintech, and digital marketing, can support the sustainability of MSMEs. The approach used is a literature review combined with descriptive analysis of relevant secondary data. The findings indicate that the use of digital technology can broaden market access, improve operational efficiency, and strengthen customer relationships. The discussion emphasizes the importance for MSMEs to shift toward or learn about the digital economy so as not to be left behind and to adapt to changing times in order to enhance global competitiveness and business sustainability. The conclusion of the study asserts that digital innovation is not merely a trend, but a crucial strategy for achieving MSME sustainability in Indonesia. This research is expected to provide practical benefits for MSME actors and serve as a reference for policy formulation that encourages digital transformation.